The Campylobacter jejuni MarR-like transcriptional regulators RrpA and RrpB both influence bacterial responses to oxidative and aerobic stresses - Gundogdu, Ozan; da Silva, Daiani T.; Mohammad, Banaz; Elmi, Abdi; Mills, Dominic C.; Wren, Brendan W.; Dorrell, Nick (Frontiers in Microbiology, 2015)
The ability of the human intestinal pathogen Campylobacter jejuni to respond to oxidative stress is central to bacterial survival both in vivo during infection and in the environment. Re-annotation of the C. jejuni NCTC11168 genome revealed the presence of two MarR-type transcriptional regulators Cj1546 and Cj1556, originally annotated as hypothetical proteins, which we have designated RrpA and RrpB (regulator of response to peroxide) respectively. Previously we demonstrated a role for RrpB in both oxidative and aerobic (O2) stress and that RrpB was a DNA binding protein with auto-regulatory activity, typical of MarR-type transcriptional regulators. In this study, we show that RrpA is also a DNA binding protein and that a rrpA mutant in strain 11168H exhibits increased sensitivity to hydrogen peroxide oxidative stress. Mutation of either rrpA or rrpB reduces catalase (KatA) expression. However, a rrpAB double mutant exhibits higher levels of resistance to hydrogen peroxide oxidative stress, with levels of KatA expression similar to the wild-type strain. Mutation of either rrpA or rrpB also results in a reduction in the level of katA expression, but this reduction was not observed in the rrpAB double mutant. Neither the rrpA nor rrpB mutant exhibits any significant difference in sensitivity to either cumene hydroperoxide or menadione oxidative stresses, but both mutants exhibit a reduced ability to survive aerobic (O2) stress, enhanced biofilm formation and reduced virulence in the Galleria mellonella infection model. The rrpAB double mutant exhibits wild-type levels of biofilm formation and wild-type levels of virulence in the G mellonella infection model. Together these data indicate a role for both RrpA and RrpB in the C. jejuni peroxide oxidative and aerobic (O2) stress responses, enhancing bacterial survival in vivo and in the environment.